PENGEMBANGAN DIGITALISASI BERBASIS MATHEMATICS TEKNOLOGI LEARNING ( MTL) DENGAN MENGGUNAKAN SISTEM QUIZ PADA APLIKASI QUIZIZ - Ni Luh Putu Ari Kartini Asri; Ni Kadek Putri Dwiani; I Wayan Sudiarsa (LPPM Universitas PGRI Mahadewa Indonesia, 2022)
The Covid-19 pandemic requires the Indonesian government to adopt a home-learning system policy at the education level. With the continuous development of technology, we are required to be people who must be able to keep up with the times, so we must be able to develop. especially for learning so that students become fun in participating in learning. Such as